Cartesian Robot for Measuring the Diameter of a Pressure Tank Using a Laser Distance Meter - Inchoorun, Natsacha; janthong, Manusak; Yamfang, Manop; preamjai ์Nopporn; Thepha, Sirichai; Pramot, Pipat (Frontiers in Engineering Innovation Research, 2021)
This research is the study and design of a cartesian robot control system for measuring the diameter of the pressure tank using a laser distance meter. The central part is a microcontroller control cabinet that communicates to the sensors kits on the cartesian robot arm. Then, the controller controls the robot arms to move through programmed positions to measure the pressure tank’s diameter. Stepping motors are used for the mechanical power system to drive the robot arm because it quickly calculates the motors’ rpm. These calculations give the coordinates of the moving position accurately with the most effective. The testing process measures the diameter of the pressure tank both before and after receiving the pressure at 8, 9, 10, 11, 12, and 13 bar to find the diameter and study the expansion characteristics of the capsule-shaped pressure tank. The size changes are measured with every increase in pressure and every designated position. The robots’ movement has an average tolerance of about 0.06 percent for a straight line motion in the X direction at a distance of 20, 50, 100, 150, and 200 millimeters, respectively. The difference between the tank’s actual size and the robot’s measurement is averagely less than 1 millimeter. at the measurement point position 1 to 10 along the X axis of the pressure vessel. The actual test result of the pressure vessel expansion measurement is not more than 1 millmeter. And the results from the simulation test with Finite Elemert, the expansion of the pressure vessel is 0.037 millmeter.